Effects of age and long-term endurance training on VO2 kinetics - Grey, T. M.; Spencer, M. D.; Belfry, G. R.; Kowalchuk, J. M.; Paterson, D. H.; Murias, J. M. (Medicine & Science in Sports & Exercise, 2015)
Purpose: This study examined the effects of age and training status on the pulmonary oxygen uptake (V.O2p) kinetics of untrained and chronically trained young, middle-age, and older groups of men.